International Accreditations as Drivers of MBA Education Improvement - WU, Yiming; WU, Chun (Advances in Social Sciences Research Journal, 2017)
Business schools in China are now under great pressure to implement continuous improvement and quality assurance to remain competitive in a globalized higher education market. Drivers for quality improvement include external pressures such as supranational organizations, national government, marketization, and globalization. As a symbol of excellent quality of management education, MBA international accreditations play an important role in quality improvement of MBA education. A case study based on GWMBA (MBA of Guangdong University of Foreign Studies) is presented to demonstrate this impact. Future challenges include the risk of standardization and institutional isomorphism and the balance between globalization and localization.